Photobiomodulation therapy in neuropathic pain: mechanisms, evidence, and future directions - Martins, Daniel O.; Rocha, Igor R. C.; Watkins, Linda R.; Chacur, Marucia (Frontiers in Photonics, 2025)
Neuropathic pain (NP) is a chronic and disabling condition resulting from injury or disease of the somatosensory system. Characterized by sensory disturbances such as allodynia, hyperalgesia, and spontaneous pain, NP remains a major clinical challenge due to the limited efficacy and significant side effects of conventional pharmacological treatments. In recent years, photobiomodulation therapy (PBMT), also referred to as low-level laser therapy (LLLT), has emerged as a promising non-pharmacological strategy for managing NP. PBMT involves the application of red or near-infrared light to biological tissues, triggering a range of photochemical and photophysical responses that enhance mitochondrial function, reduce oxidative stress, modulate inflammation, and support neural repair. This review provides a comprehensive synthesis of the current evidence on PBMT for NP, integrating mechanistic insights with preclinical findings. We discuss the biological underpinnings of PBMT, including mitochondrial activation via cytochrome c oxidase, modulation of cytokines and oxidative stress markers, and upregulation of neurotrophic factors such as BDNF. Preclinical studies in well-established NP models (e.g., chronic constriction injury, spared nerve injury, diabetic neuropathy) demonstrate consistent analgesic effects and neuroprotective outcomes following both local and remote/systemic PBMT applications. We also highlight key limitations and knowledge gaps in the field, including the need for standardized protocols, greater exploration of remote PBMT strategies, and improved consideration of sex-based responses. Finally, we outline future directions, such as integration with multimodal therapies, personalized dosimetry, and the development of wearable and transcranial PBMT technologies. Together, the existing body of evidence supports PBMT as a safe and potentially effective tool for NP management, while underscoring the need for more rigorous and translational research.